2002
DOI: 10.1037/0002-9432.72.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Disorganized reasoning in Holocaust survivors.

Abstract: The long-term psychological effects associated with the Holocaust are still under debate (for a review, see Bar-On et al., 1998). For example, Krell (1993) showed that most Holocaust survivors have managed to raise families and successfully adapt to their social environments (cf. Leon, Butcher, Kleinman, Goldberg, & Almagor, 1981). At the same time, longterm effects of the Holocaust have been discovered, including chronic anxiety and depression (Niederland, 1968), personality disorders (Dor Shav, 1978), and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…Mazor et al (1990) proposed that the use of defensive mechanisms, such as denial and repression, enabled Holocaust survivors to focus on active adaptation when rebuilding their lives, establishing new homes, and raising new families. Similarly, Sagi et al (2002) suggested that the preference of some survivors to dismiss attachment-related issues may serve as a defensive strategy to protect themselves against potentially present and future dissatisfaction and distress in close relationships. Alternatively, resilience of survivors in the domains of physical health and cognitive functioning might be considered a prerequisite for successful adaptation to family life and work, despite their elevated symptoms of posttraumatic stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mazor et al (1990) proposed that the use of defensive mechanisms, such as denial and repression, enabled Holocaust survivors to focus on active adaptation when rebuilding their lives, establishing new homes, and raising new families. Similarly, Sagi et al (2002) suggested that the preference of some survivors to dismiss attachment-related issues may serve as a defensive strategy to protect themselves against potentially present and future dissatisfaction and distress in close relationships. Alternatively, resilience of survivors in the domains of physical health and cognitive functioning might be considered a prerequisite for successful adaptation to family life and work, despite their elevated symptoms of posttraumatic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Other findings showed that many survivors also experienced a state of unresolved mourning. The loss of loved ones generated intense feelings of sadness, helplessness, and rage, alongside feelings of survival guilt (Kapeliuk, 1995;Sagi, Van IJzendoorn, Joels, & Scharf, 2002;. Studies examining the frequency of PTSD and other psychiatric symptoms in Holocaust survivors showed that survivors had more symptoms than did comparison groups (Breslau, 2002;M.…”
Section: Maladaptive Consequencesmentioning
confidence: 99%
“…In line with the study's goals we only used the Unresolved State of Mind score (USM) and it was computed using the guidelines provide by Main et al (1993). The BLAAQ-U has been validated on a sample of Holocaust survivors in which survivors of the Holocaust were rated higher on the USM scale and endorsed more Unusual Beliefs than a comparison group (Sagi, van IJzendoorn, Joels, & Scharf, 2002).…”
Section: Assessments Of Maternal Resolutionmentioning
confidence: 99%
“…Later-life influences of the Holocaust on child survivors of all ages have been extensively studied in Israel and abroad (see Dasberg, 2001, for a review). The psychological functioning of child survivors, in comparison with that of matched peers who had not experienced the Holocaust, has recently been the focus of a number of studies (Amir & Lev-Wiesel, 2003;Brom, Durst, & Aghassy, 2002;Cohen, Brom, & Dasberg, 2001;Cohen, Dekel, & Solomon, 2002;Sagi, Van IJzendoorn, Joels, & Scharf, 2002;SagiSchwartz, Van IJzendoorn, Grossmann, Joels, Grossmann, et al, 2003). Results consistently show that child Holocaust survivors suffer significantly more from posttraumatic stress disorders than their non-Holocaust-exposed peers.…”
mentioning
confidence: 96%